Different levels of selenomethionine on the meat quality and selenium deposition in tissue of finishing pigs - Silva, Vanessa Avelar; Bertechini, Antonio Gilberto; Sampaio Clemente, Alisson Helio; Villas Boas de Freitas, Luis Filipe; Franco Nogueira, Bernardo Rocha [UNESP]; Oliveira, Barbara Lopes de; Souza Ramos, Alcineia de Lemos (Wiley-Blackwell, 2019)
The aim of the study was to verify the influence of selenomethionine (SM) supplementation on performance, carcass yield, characteristics of meat quality and Se tissue deposition of finishing pigs. A total of 128 hybrid pigs with an average weight of 76 kg were distributed in randomized blocks according to body weight in eight treatments and eight replicates. The experimental treatments were two Se levels from sodium selenite-SS (0.3 and 0.6 ppm), four Se levels from SM (0.3, 0.4, 0.5 and 0.6 ppm) and two combinations of SS with SM (SS 0.15 + SM 0.15 ppm and SS 0.3 + SM 0.3 ppm) providing 0.3 and 0.6 ppm Se in the diet respectively. The feeds were based on corn and soya bean meal. After 30 days on test, were analysed the performance indices and the pigs were slaughtered at commercial slaughterhouse. The cold carcass yield, the physicochemical characteristics of the loin meat and the Se content in muscle and liver were evaluated. There was no significant difference in performance indices (p > .05); however, there was a linear effect on the increase in pig carcass yield by increasing SM (p < .05). The use of SM solely or combined with SS provided higher Se deposition in muscle compared to SS (p < .05). The highest Se deposition in muscle occurred for SM at 0.4 ppm (p < .05). The SS provided higher Se deposition in liver (p < .05). The SM presented best results for meat quality compared to other sources (p < .05). The level of 0.4 ppm Se promoted the best results for the indices of yellow, luminosity, cooking loss and pH (p < .05). The use of SM at any level promotes higher oxidation stability of pig meat (p < .05). The supplementation of SM at a level of 0.4 ppm promotes better physicochemical characteristics and higher Se deposition on swine meat.
Keywords: meat quality; organic selenium; oxidation stability